2017
DOI: 10.1002/crq.21190
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about Victim‐Offender Conferences: Factors Influencing Victim‐Offender Engagement

Abstract: Victim-off ender conferences provide victims an opportunity to pursue their justice goals while talking directly with their off ender. Although research on victims' conference participation willingness is growing, it has tended to neglect the infl uence of context factors. Drawing on the theory of planned behavior, the study reported in this article elicited beliefs about justice goals, emotions, perceived support, and external control beliefs related to intent to participate in a victim-off ender conference. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Such socialization raises the question about the relative importance people place on offender-related outcomes such as apologizing and victim-related outcomes such as information sharing. For example, Paul and Schenck-Hamlin (2017) found that people generally feel that youth who commit an offense should be punished and that victims should receive restitution. Likewise, Hansen and Umbreit (2018) assert that victims typically bring justice-related expectations and goals into mediation sessions.…”
Section: Restorative and Conventional Justicementioning
confidence: 99%
See 3 more Smart Citations
“…Such socialization raises the question about the relative importance people place on offender-related outcomes such as apologizing and victim-related outcomes such as information sharing. For example, Paul and Schenck-Hamlin (2017) found that people generally feel that youth who commit an offense should be punished and that victims should receive restitution. Likewise, Hansen and Umbreit (2018) assert that victims typically bring justice-related expectations and goals into mediation sessions.…”
Section: Restorative and Conventional Justicementioning
confidence: 99%
“…Based on previous research, participants were asked to rate the importance of five outcomes: (a) preventing the offender from committing another offense in the future (Latimer et al, 2005); (b) learning, growing, and maturing (Borton & Paul, 2015;Wenzel et al, 2008); (c) paying restitution for the damage they caused (Shapland et al, 2006); (d) experiencing punishment and negativity for their actions (Barton, 1999;Paul & Schenck-Hamlin, 2017); and (e) apologizing to their victims (Bolívar et al, 2013). Based on exploratory factor analysis, preventing recidivism and facilitating learning were grouped into a single variable with sufficient reliability (α = 0.71) of helping offenders experience restoration by getting on a better path, thereby creating four offender outcomes.…”
Section: Offender-related Outcome Importancementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, how does socialization influence these definitions? As noted above, desiring to see the wrongdoer suffer punishment is a common response to offensive behavior (Aquino et al., ; Paul & Schenck‐Hamlin, ). Such a response reflects “just world beliefs” that people should “get what they deserve” (Lerner, ; Strelan, ).…”
Section: Defining Restorative Justicementioning
confidence: 99%